129 HISTONE DEACETYLASE INHIBITORS VALPROIC ACID AND TRICHOSTATIN A PERMIT ALVEOLAR FORMATION IN PRETERM LAMBS MANAGED FOR 72 HOURS BY MECHANICAL VENTILATION. Issue 1 (1st January 2007) - Albertine, K. H.; Amundsen, S.; Dong, L.; Dahl, M. J.; McKnight, R. A.; Null, D. M.; Yoder, B.; Lane, R. H.
Abstract : Objective: Chronic lung disease (CLD) of prematurity is characterized by DNA hypermethylation and H3 hypoacetylation. Long-term changes in gene expression and phenotypic changes suggest persistent changes in gene expression by altering determinants of chromatin structure. We hypothesized that disruption of histone deacetylation will permit alveolar formation. Materials/Methods: Preterm lambs (≈132 days' gestation; term ≈148 days), treated with antenatal steroids and postnatal surfactant, were managed by mechanical ventilation (MV) for 3 days and treated daily with valproic acid (VPA; 25 mg/kg, IV; n = 4), trichostatin A (TSA; 0.10 mg/kg, IV; n = 4), or vehicle ( n = 4). The positive gold standard was management by nasal CPAP ( n = 4). At the end of 3 days, the lungs were analyzed morphometrically. Results: VPA-treated and TSA-treated preterm lambs had more advanced alveolar formation than vehicle controls, as shown by morphometric measurements of radial alveolar count (6 ± 2 and 6 ± 1 vs 2 ± 1, respectively; p < .05), secondary septal volume density (11 ± 3 and 10 ± 3 vs 5 ± 2, respectively; p < .05), and alveolar wall thickness (2.89 ± 0.07 and 2.97 ± 0.08 vs 3.88 ± 0.10, respectively; p < .05). Alveolar formation in the VPA- or TSA-treated lambs was comparable to that in nasal CPAP-managed preterm lambs. Conclusions: Management of preterm lambs with MV leads to alveolar simplification. Treating preterm lambs with valproic acid or trichostatin A, histone deacetylase inhibitors, permitted alveolar formation. We conclude that histone acetylation, which affects patterns of gene expression, is necessary for alveolar formation. HL62875, HL56401, HD41075, CHRC.